The Epidemiology of Bile Acid Diarrhea in Denmark [Letter] - Nurmayanti D; Aziz A; Khayan K (Clinical Epidemiology, 2023)
Demes Nurmayanti,1 Alkausyari Aziz,2 Khayan Khayan3 1Department of Environmental Health, Poltekkes Kemenkes Surabaya, Surabaya, Indonesia; 2Department of Nutrition, Poltekkes Kemenkes Riau, Pekanbaru, Indonesia; 3Department of Medical Laboratory Technology, Poltekkes Kemenkes Banten, Serang, IndonesiaCorrespondence: Demes Nurmayanti, Tel +62 8113627796, Email demes@poltekkesdepkes-sby.ac.id